Consumer Protection for the Use of Hazardous Asbestos Building Materials (Based on Supreme Court Decision Number 6 P/HUM/2024) - Azzahra, Nabila Adifia; Tarina, Dwi Desi Yayi (Universitas Muhammadiyah Sumatera Utara, 2025)
The purpose of this study is to analyze the process of legal protection for the community and victims of the use of asbestos products based on Supreme Court Decision Number 6 P/HUM/2024. This study uses a normative legal research method (normative juridical) with a statutory, case, and conceptual approach. The results of the study indicate that the process of legal protection for the community and victims has not been running well and there is still much that needs to be improved. If in accordance with Supreme Court Decision Number 6 P/HUM/2024, legal protection can be carried out through institutions that provide legal assistance. Legal protection for consumers can also be resolved through litigation or non-litigation. This is in accordance with the regulatory arrangements contained in Law Number 8 of 1999 concerning Consumer Protection (UUPK), Government Regulation Number 58 of 2001 concerning Guidance and Supervision of the Implementation of Consumer Protection, and Regulation of the Minister of Health Number 472 of 1996 concerning Safeguarding Materials Hazardous to Health. Therefore, business actors or producers must also be responsible for the welfare of society as consumers by replacing asbestos materials with safer alternatives